2015
DOI: 10.5937/ratpov52-8000
|View full text |Cite
|
Sign up to set email alerts
|

The effect of drought on water regime and growth of quinoa (Chenopodium quinoa willd.)

Abstract: Summary: Quinoa (Chenopodium quinoa Willd.) is a highly nutritious Andean seed crop which shows great potential to grow under a range of different stress environments. The objective of this study was to investigate the effect of drought on water regime and the growth of quinoa variety KVL52 in controlled conditions. The results of the present experiment indicate that the reaction of quinoa plants to drought are based on drought avoidance mechanisms: reduced transpiration and sustained water uptake. Transpirati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…LAI is the site of photosynthetic activity; this parameter is of major importance in the selection of salt tolerant varieties and could be considered more reliable than the vegetation height (Ben Naceur et al, 2001). Our outcomes are in accord with those of El Youssfi (2013), Algosaibi et al (2015), and Stikic et al (2015). Those authors declared that increased NaCl concentration in water decreased the leaf area of quinoa and consequently decreased LAI.…”
Section: Discussionsupporting
confidence: 92%
“…LAI is the site of photosynthetic activity; this parameter is of major importance in the selection of salt tolerant varieties and could be considered more reliable than the vegetation height (Ben Naceur et al, 2001). Our outcomes are in accord with those of El Youssfi (2013), Algosaibi et al (2015), and Stikic et al (2015). Those authors declared that increased NaCl concentration in water decreased the leaf area of quinoa and consequently decreased LAI.…”
Section: Discussionsupporting
confidence: 92%
“…Drought‐induced growth inhibition was less pronounced for the roots (63%) compared to the shoots (73%), leading to an enhanced root‐to‐shoot weight ratio. Similarly, Stikić, Jovanović, Marjanović, and Dordević () found that root biomass of C. quinoa did not change significantly in response to drought as the shoot parts did. Such reaction of biomass allocation between root and shoot is considered to be an adaptive feature to sustain water uptake under decreasing water availability (Jacobsen & Stølen, ; Munns, ).…”
Section: Discussionmentioning
confidence: 93%
“…Quinoa reacts to drought in several ways; drought avoidance by reducing the transpiration rate as a result of decreasing the stomatal conductance and by sustaining water uptake (Razzaghi et al, 2011 andStikić et al, 2015). They concluded that quinoa should be irrigated when or before the relative available water reaches 0.42.…”
mentioning
confidence: 99%